Fabrication of 3D PEDOT:PSS composite microstructures via two-photon polymerisation - Delaney, Colm (My University, 2026)
Two-photon polymerisation is a cutting-edge fabrication technique that enables the creation of complex 3D polymer microstructures. The miniaturisation of electronics, enabling advances in microrobotics and discreet monitoring systems necessitates the production of conductive microstructures. Herein, two photoresist formulations containing poly(3,4-ethylenedioxythiophene) doped with poly(styrene sulfonate) (PEDOT:PSS) are proposed for fabricating microstructures via two photon polymerisation. An in-depth characterisation of the resulting microstructures and their composition are presented using Raman spectroscopy, scanning electron microscopy and atomic force microscopy. Additionally, the conductivity of the microstructures is further analysed through conductive atomic force microscopy (C-AFM), and Kelvin probe force microscopy (KPFM).
PUBLISHED